Pengaruh Kecukupan Modal, Risiko Kredit, Efisiensi Operasional Dan Likuiditas Terhadap Profitabilitas (Survey pada Bank Umum Konvensional di Indonesia Periode 2011-2015) - 'Aini, Indah Nur; , Dr. Erma Setiawati, MM.,CA (2017)
The study was conducted to test the effect of Capital Adequacy, Credit Risk, Operational Efficiency and Liquidity towards Profitability. Profitability is an indicator that can be used to measure the performance of a bank. The population used in this study is the state-owned banks listed on Bank Indonesia (BI). The sampling method that used in this study is purposive sampling and obtained a sample of 4 banks that have met the criteria. The data is quarterly data obtained from published financial statements of state-owned banks during the years 2011-2015. Data analysis with multiple regression. The result of study shows that simultaneously variable Capital Adequacy, Credit Risk, Operational Efficiency, and Liquidity significant influence toward Profitability. Partially independent variables that significant influence toward Profitability are Capital Adequacy, Operational Efficiency, And Liquidity toward profitability. Meanwhile variable Credit Risk has not been influence toward profitability. Adjusted R-Square value of 91,8 % suggests that the variable profitability can be explained by variable Capital Adequacy, Credit Risk, Operational Efficiency and Liquidity of 91,8 % , while the rest of 8,2 % described by other variables outside model research.